Placental mesenchymal dysplasia complicated with sudden fetal demise and amniotic fluid embolism: a case report - Shao-Jing Wang; Li-Ling Lin; Wei-Chih Chen (BMC, 2022)
Abstract Background Placenta mesenchymal dysplasia (PMD) is a rare placental anomaly associated with various fetal and maternal complications. Whether close ultrasound surveillance can prevent intrauterine fetal demise (IUFD) in patients with PMD is still under investigation. Amniotic fluid embolism (AFE) is a rare, lethal, and unpredictable maternal complication that has never been described in association with PMD. Here, we report a case of PMD, in which the fetus eventually demised in utero despite weekly color Doppler monitoring, and the mother subsequently encountered AFE during delivery. Case presentation A 43-year-old woman who had received three frozen embryo transfer, was found to have a singleton pregnancy with an enlarged multi-cystic placenta at 8 weeks' gestation. Fetal growth restriction (FGR) was noted since the 21stweek. The fetus eventually demised in-utero at 25 weeks despite weekly color Doppler surveillance. Cesarean section was performed under general anesthesia due to placenta previa totalis and antepartum hemorrhage. During surgery, the patient experienced a sudden blood pressure drop and desaturation followed by profound coagulopathy. AFE was suspected. After administration of inotropic agents and massive blood transfusion, the patient eventually survived AFE. PMD was confirmed after pathological examination of the placenta. Conclusions While FGR can be monitored by color Doppler, our case echoed previous reports that IUFD may be unpreventable even under intensive surveillance in PMD cases. Although AFE is usually considered unpredictable, PMD can result in cumulative risk factors contributing to AFE. Whether a specific link exists between the pathophysiology of PMD and AFE requires further investigation.